2017
DOI: 10.3892/etm.2017.4807
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group proteins: Novel molecules associated with ultraviolet A-induced photoaging of human skin

Abstract: Epigenetic repressor polycomb group (PcG) proteins are thought to serve a role in a number of cellular processes, including carcinogenesis, senescence, apoptosis and DNA repair. In the present study, long-wave ultraviolet A (UVA) was used to irradiate human skin fibroblasts (HSFs) and embryonic skin fibroblasts (ESFs) in order to simulate photoaging of the skin. The results of cell proliferation, apoptosis, hyaluronic acid (HA) content and reverse transcription-quantitative polymerase chain reaction assays rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…These findings provide evidence that Bmi-1 plays a protective role against intrinsic skin aging. Consist with previous studies [14,23], in our study, we confirmed that hair follicles, keratinocytes, and fibroblasts have relatively stronger expression levels of Bmi-1 localization. Long considered both physiologic and inevitable, skin aging is a degenerative phenomenon progressively with age [24].…”
Section: Discussionsupporting
confidence: 91%
“…These findings provide evidence that Bmi-1 plays a protective role against intrinsic skin aging. Consist with previous studies [14,23], in our study, we confirmed that hair follicles, keratinocytes, and fibroblasts have relatively stronger expression levels of Bmi-1 localization. Long considered both physiologic and inevitable, skin aging is a degenerative phenomenon progressively with age [24].…”
Section: Discussionsupporting
confidence: 91%
“…All samples were analyzed in duplicate, and the results are presented as relative gene expression using the ΔΔct method. HPRT1 , HMBS , and RPL13A primer sequences were based on the work of Vandesompele et al [ 17 ], while other primers were based on sequences published elsewhere: CD44s [ 18 ], RHAMM [ 19 ], ICAM-1 [ 20 ], LYVE-1 [ 21 ], TLR4 [ 22 ], HYAL1 , HYAL2 [ 23 ], and HYAL3 [ 24 ]. Other sequences were designed using Primer3 software [ 25 ] or PrimerBlast [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, UV-A radiations modulate the expression of EZH2 and Bmi-1 , induce the senescence of human dermal fibroblasts and reduce hyaluronic acid (HA) synthesis. The use of GSK126, an inhibitor of the EZH2-methyl transferase activity, restores dermal fibroblasts growth after UV-A irradiation by modulating the expression of enzymes involved in HA synthesis and inhibiting the transcription of various photo-aging-related genes (e.g., Smad2 , Smad4 , MMP-1 ) [102,103]. Moreover, UV-B radiations induce human dermal fibroblast senescence through miR-101 induction and EZH2 reduction [104].…”
Section: Epigenetic Changes In Skin Agingmentioning
confidence: 99%